Influence of rheumatoid arthritis on women's sexual function: A systematic review and meta-analysis - Fatemeh Zahra Karimi; Salmeh Dadgar; Mahboubeh Abdollahi; Zahra Norouzi (Mashhad University of Medical Sciences, 2019)
Introduction: Sexual problems are among the most important outcomes of rheumatoid arthritis in the affected women. Incidence of this disease in women is reported 2-3 times higher than that in men. This systematic review and meta-analysis was carried out to investigate the influence of rheumatoid arthritis on women's sexual function. Methods: In this systematic review and meta-analysis, the published articles in the databases, such as Web of Science, Cochrane, PubMed, Scopus, Magiran, SID, and Google Scholar, were searched using the English keywords of "Sexual dysfunction, Sexual behavior, Sexual problems, Rheumatoid arthritis, Sexual functioning, Sexual activity, and Sexual disorder" and their Persian equivalents until December 2018. Data analysis was done using STATA (version 14.1). The I2 index was used to assess the heterogeneity between the studies, and the random effects model was applied to pool the data and perform meta-analysis. Results: A total of 16 articles were included in the systematic review, and 10 articles with 1580 participants were included in the meta-analysis. Meta-Analysis results showed that based on the random effects model, rheumatoid arthritis leads to the decrease of female sexual function (SMD=-1.01; 95% CI: (-1.24, -0.77); P=0.001) , (RR=1.95; 95% CI: (1.65, 2.30); P<0.0001). Conclusion: Rheumatoid arthritis leads to the reduction of female sexual function. Therefore, healthcare providers should consider this group of patients for the incidence of female sexual problems and design and implement programs to promote their sexual function.